Cathode roller, electrolytic copper foil mechanism and electrolytic copper foil preparation method, finished copper foil preparation system and preparation method
By forming a graphene film on the cathode roller, copying the surface morphological characteristics of the substrate copper foil, preparing electrolytic copper foil, and preparing single crystal or large-domain copper foil under low temperature annealing conditions, the wrinkle problem when the thickness is less than 25 μm and the cost of high-temperature annealing is solved, and the preparation efficiency and product performance are improved.
Patent Information
- Application Number
- CN202111285831.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-02
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2041-11-02
AI Technical Summary
In the preparation of single crystal or large-domain copper foil, the thickness is less than 25 μm, which is unable to meet the needs of lighter and thinner. Conventional practices require high-temperature annealing, which is cheaper and less efficient.
The electrolytic copper foil is prepared by a cathode roller with a graphene film. The graphene film replicates the surface morphological characteristics of the substrate copper foil to achieve "pre-single crystallization" of the electrolytic copper foil, thereby preparing single crystal or large-crystalline copper foil under low temperature annealing conditions.
The annealing temperature is significantly reduced, and the wrinkle problem caused by thermal stress is avoided. Single crystal or large-domain copper foil with a thickness of <25 μm can be obtained under low-temperature annealing conditions, which meets the needs of lightweighting and improves the preparation efficiency.
Smart Images

Figure CN113846357B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of copper foil preparation, and in particular, to a cathode roller, an electrolytic copper foil mechanism and a method for preparing an electrolytic copper foil, and a system and method for preparing a finished copper foil. Background Art
[0002] Copper, as a metal material with excellent electrical, thermal and ductile properties, is widely used in many fields of the national economy, such as the electronics industry, and is an indispensable basic material for national economic development and high-tech competition. With the rapid development of emerging industries such as the new generation of electronic information technology, high-end equipment manufacturing, and new energy vehicles, higher requirements are placed on the electrical conductivity, thermal conductivity and other properties of copper materials.
[0003] The application of single crystal or large crystal domain copper foil on circuit boards can reduce the amount of copper etching in the manufacturing process, better demonstrating the advantages of highly conductive fine lines; when single crystal or large crystal domain copper foil is used as the negative electrode collector of lithium-ion batteries, it can also better demonstrate the advantages of low internal resistance and light weight.
[0004] However, under existing technical conditions, the thickness of single crystal or large crystal domain copper foil prepared by high temperature annealing is generally ≥25μm. If the thickness is less than 25μm, a large number of wrinkles are easily generated, and single crystal or large crystal domain copper foil that meets the demand cannot be obtained. Therefore, the conventional practice is to obtain single crystal or large crystal domain copper foil with a thickness of ≥25μm, and then perform calendering and other operations on the single crystal or large crystal domain copper foil to meet the demand for lighter and thinner materials. Summary of the invention
[0005] The present application provides a cathode roller, an electrolytic copper foil mechanism and a method for preparing an electrolytic copper foil, and a system and method for preparing a finished copper foil, which can solve at least one of the above-mentioned technical problems.
[0006] The embodiment of the present application is implemented as follows:
[0007] In a first aspect, the present application provides an example of a cathode roller, which includes: a roller-shaped body, an annular base copper foil, and a graphene film.
[0008] The annular base copper foil is formed on the peripheral wall of the main body and is conductively connected to the main body; the graphene film is formed on the surface of the base copper foil and replicates the surface morphology characteristics of the base copper foil.
[0009] The material of the base copper foil is single crystal copper foil or large crystal domain copper foil, and the number of grain boundaries of the large crystal domain copper foil per square decimeter is ≤5.
[0010] Since grain orientation affects the surface morphology of copper foil, when the cathode roller is used to prepare electrolytic copper foil, the morphology of the graphene film surface will affect the crystal domain and grain boundary distribution of the obtained electrolytic copper foil, thereby changing the microstructure of the electrolytic copper foil.
[0011] In the above-mentioned setting, based on the thin thickness of the graphene film, when it is formed on the surface of the substrate copper foil, the graphene film inevitably replicates and forms surface morphology characteristics that are the same or approximately the same as the surface morphology characteristics of the substrate copper foil. When it is used to prepare electrolytic copper foil, the electrolytic copper foil deposited on the surface of the graphene film is not only easy to peel off, but the electrolytic copper foil can also replicate the surface morphology characteristics of the graphene film, thereby making its crystal domain and grain boundary distribution similar to those of the substrate copper foil, thereby achieving "pre-crystallization" of the lattice orientation of the electrolytic copper foil, so that in the subsequent preparation of single crystal or large crystal domain copper foil, the annealing temperature can be significantly reduced, and single crystal copper foil or large crystal domain copper foil can be obtained under low temperature annealing conditions. Moreover, due to the reduction in annealing temperature, even if the thickness of the electrolytic copper foil is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0012] In a second aspect, the present application provides an electrolytic copper foil mechanism, which includes an electrolytic cell, the cathode roller provided in the first aspect of the present application, and an anode part.
[0013] The electrolytic cell is used to hold an electrolytic solution, and the cathode roller utilizes the electrolyte to deposit electrolytic copper foil by electroplating, and the anode part is energized with the cathode roller through the electrolyte.
[0014] In the above-mentioned setting, the cathode roller is used to prepare the electrolytic copper foil, which is not only conducive to the subsequent peeling of the electrolytic copper foil and avoids damage to the electrolytic copper foil during peeling, but also the obtained electrolytic copper foil has surface morphology characteristics similar to those of the substrate copper foil, thereby realizing the "pre-crystallization" of the electrolytic copper foil, so that when the single crystal or large crystal domain copper foil is subsequently prepared, the annealing temperature can be significantly reduced, and the single crystal copper foil or the large crystal domain copper foil can be obtained under low temperature annealing conditions. Moreover, since the annealing temperature is reduced, even if the thickness of the electrolytic copper foil is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0015] In a third aspect, the present application provides an example of a system for preparing a finished copper foil, which includes the electrolytic copper foil mechanism, the stripping mechanism, and the annealing mechanism shown in the second aspect of the present application.
[0016] Among them, the stripping mechanism is used to strip the electrolytic copper foil on the cathode roller, the annealing mechanism has an annealing chamber for receiving the stripped electrolytic copper foil, and the annealing mechanism is provided with an inert gas input pipeline connected to the annealing chamber, a hydrogen input pipeline, and a heating component for heating the annealing chamber.
[0017] In the above-mentioned setting method, the electrolytic copper foil mechanism, the stripping mechanism and the annealing mechanism cooperate to strip the electrolytic copper foil prepared by the electrolytic copper foil mechanism, and then anneal the stripped electrolytic copper foil to obtain the finished copper foil. The preparation system has a simple structure and is easy to operate, thereby improving the preparation efficiency of the finished copper foil.
[0018] In a fourth aspect, the present application example provides a method for preparing an electrolytic copper foil, which comprises: in the electrolytic copper foil mechanism provided in the second aspect of the present application, after the cathode roller and the anode are immersed in the electrolyte, electrolysis is performed to deposit electrolytic copper foil on the surface of the graphene film, and the electrolytic copper foil is peeled off.
[0019] In the above-mentioned setting method, the operation is simple. The cathode roller of the above-mentioned electrolytic copper foil mechanism is used to prepare the electrolytic copper foil, which is not only conducive to the subsequent peeling of the electrolytic copper foil and avoids damage to the electrolytic copper foil during peeling, but also the obtained electrolytic copper foil has a surface morphology feature similar to that of the substrate copper foil, thereby realizing the "pre-crystallization" of the electrolytic copper foil, so that when the single crystal or large crystal domain copper foil is subsequently prepared, the annealing temperature can be significantly reduced, and the single crystal copper foil or the large crystal domain copper foil can be obtained under low-temperature annealing conditions. Moreover, since the annealing temperature is reduced, even if the thickness of the electrolytic copper foil is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0020] In a fifth aspect, the present application example provides a method for preparing a finished copper foil, wherein the number of grain boundaries per square decimeter of the finished copper foil is 0≤≤5.
[0021] The method for preparing the finished copper foil comprises: placing the electrolytic copper foil prepared by the preparation method provided in the fourth aspect of the present application in an annealing chamber, introducing an inert gas into the annealing chamber and heating the chamber, wherein the inert gas flow rate is 300-500 sccm.
[0022] When the temperature is raised to 300-800°C, the inert gas flow rate remains unchanged, H2 is introduced with a H2 flow rate of 10-500sccm, and then cooled after annealing for a preset time.
[0023] In the above-mentioned setting, the obtained electrolytic copper foil has surface morphology characteristics similar to those of the base copper foil, thereby realizing "pre-single crystallization" of the electrolytic copper foil, so that the annealing temperature can be significantly reduced when preparing single crystal or large crystal domain copper foil in the subsequent preparation. Therefore, annealing can be performed at 300-800°C to obtain the finished copper foil, which can not only effectively reduce energy consumption, but also because the annealing temperature is significantly lower than the existing annealing temperature, even if the thickness of the electrolytic copper foil is less than 25μm, the problem of wrinkling of the electrolytic copper foil during the annealing process can be avoided, and single crystal or large crystal domain copper foil with a thickness of less than 25μm can be directly prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A schematic diagram of the structure of a system for preparing a finished copper foil provided in Example 1;
[0026] Figure 2 A schematic diagram of the structure of the electrolytic copper foil mechanism provided in Example 1;
[0027] Figure 3 The XRD pattern of the finished copper foil provided in Example 2;
[0028] Figure 4 The XRD pattern of the finished copper foil provided in Example 3;
[0029] Figure 5 This is the XRD pattern of the finished copper foil provided in Comparative Example 1.
[0030] Icons: 10-finished copper foil preparation system; 100-electrolytic copper foil mechanism; 110-frame; 120-electrolytic cell; 130-electrolyte; 140-cathode roller; 141-main body; 143-substrate copper foil; 145-graphene film; 150-anode part; 160-peeling mechanism; 210-cleaning mechanism; 220-post-processing mechanism; 300-drying mechanism; 400-winding mechanism; 500-annealing mechanism; 510-annealing chamber; 512-feeding end; 513-discharging end; 520-high temperature resistant hanging rail; 530-unwinding wheel; 600-electrolytic copper foil. DETAILED DESCRIPTION
[0031] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0033] At present, using single crystal copper foil or large-size crystal domain copper foil as substrate can reduce the influence of grain boundaries, and has higher electrical and thermal conductivity, corrosion resistance and other properties, showing good application prospects in semiconductor, microelectronics, high-end electrical and mechanical equipment and other industries.
[0034] The applicant has found that the existing preparation method of single crystal or large crystal domain copper foil is usually obtained by high temperature annealing, that is, annealing is performed at a high temperature of about 1000°C to obtain single crystal or large crystal domain copper foil, wherein the thickness of the substrate copper foil used for high temperature annealing (the substrate copper foil is the copper foil used for high temperature annealing to obtain single crystal or large crystal domain copper foil) needs to be ≥25μm. If the substrate copper foil with a thickness of less than 25μm is used for annealing, the obtained single crystal or large crystal domain copper foil is prone to wrinkling, affecting its electrical conductivity, etc., and therefore cannot meet the actual design requirements of lighter and thinner. Therefore, the general practice is to perform calendering and other operations on the single crystal or large crystal domain copper foil after high temperature annealing to make it lighter and thinner to meet the demand for lighter and thinner products, and the operation is relatively cumbersome.
[0035] The applicant has studied the above problems and found that, since grain orientation affects the surface morphology of copper foil, if the surface morphology of the electrolytic copper foil is similar to that of single crystal copper foil or large crystal domain copper foil, the subsequent annealing temperature can be significantly reduced, and the wrinkles caused by thermal stress and other reasons can be avoided under the premise of significantly reducing the subsequent annealing temperature. Therefore, when the thickness of the electrolytic copper foil is less than 25μm, low-temperature annealing can significantly reduce the generation of wrinkles in the finished copper foil, and due to the "pre-single crystalization" of the electrolytic copper foil, low-temperature annealing can directly obtain a single crystal or large crystal domain finished copper foil with a thickness of less than 25μm.
[0036] Based on this, the applicant has designed a cathode roller, which includes a roller-shaped body, a substrate copper foil (single crystal copper foil or large crystal domain copper foil) formed on the peripheral wall of the body and conductively connected to the body, and a graphene film formed on the surface of the substrate copper foil and replicating the surface morphology characteristics of the substrate copper foil. The graphene is arranged in the outermost layer. On the one hand, it is conducive to the subsequent peeling of the electrolytic copper foil to avoid damage to the electrolytic copper foil during peeling. On the other hand, since the graphene film has the surface morphology characteristics of the substrate copper foil, the electrolytic copper foil electrodeposited on the surface of the graphene film will also replicate the surface morphology of the graphene film, thereby realizing "pre-crystallization" of the electrolytic copper foil in terms of lattice orientation, so that the annealing temperature can be significantly reduced during the subsequent annealing preparation to obtain single crystal copper foil or large crystal domain copper foil. Therefore, even if the thickness of the electrolytic copper foil is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0037] The electrolytic copper foil and finished copper foil prepared in the embodiments of the present application can be used in, but not limited to, industries such as semiconductors, microelectronics, high-end electrical and mechanical equipment, and can also be used as copper foil for circuit boards or copper current collectors for negative electrodes of batteries.
[0038] The following examples 2-4 and comparative examples 1-2 all adopt Figure 1 The same finished copper foil preparation system shown in the figure is used to prepare the finished copper foil, wherein the base copper foil is made of the same large crystal domain copper foil, and the number of grain boundaries per square decimeter of the large crystal domain copper foil is ≤5.
[0039] The following is a specific description of the cathode roller, the electrolytic copper foil mechanism and the electrolytic copper foil preparation method, and the finished copper foil preparation system and preparation method of the embodiment of the present application:
[0040] Example 1
[0041] See also Figure 1 A system 10 for preparing a finished copper foil includes an electrolytic copper foil mechanism 100 , a stripping mechanism 160 , and an annealing mechanism 500 .
[0042] Among them, 0≤the number of grain boundaries per square decimeter of the finished copper foil is ≤5. That is, the finished copper foil is a single crystal copper foil or a large crystal domain copper foil.
[0043] See also Figure 2 The electrolytic copper foil mechanism 100 includes an electrolytic cell 120 , a cathode roller 140 and an anode part 150 .
[0044] The electrolytic cell 120 is used to contain an electrolyte 130 . The cathode roller 140 uses the electrolyte 130 to electro-deposit the electrolytic copper foil 600 by electroplating. The anode part 150 is energized with the cathode roller 140 through the electrolyte 130 .
[0045] Optionally, the electrolytic copper foil mechanism 100 includes a frame 110, on which an electrolytic cell 120, a cathode roller 140 and an anode part 150 are provided, wherein the cathode roller 140 is rotatably arranged above the electrolytic cell 120, the anode part 150 is located in the electrolytic cell 120, and the anode part 150 is energized with the cathode roller 140 through the electrolyte 130.
[0046] The cathode roller 140 includes a roller-shaped body 141 , an annular base copper foil 143 , and a graphene film 145 .
[0047] Among them, the annular substrate copper foil 143 is formed on the peripheral wall of the body 141 and is conductively connected to the body 141; the graphene film 145 is formed on the surface of the substrate copper foil 143 and wraps the substrate copper foil 143, and the graphene film 145 replicates the surface morphology characteristics of the substrate copper foil 143. The material of the substrate copper foil 143 is a single crystal copper foil or a large crystal domain copper foil, and the number of grain boundaries of the large crystal domain copper foil per square decimeter is ≤5. At this time, the cathode roller 140 is used to prepare the electrolytic copper foil 600, and the obtained electrolytic copper foil 600 will have surface morphology characteristics similar to those of the substrate copper foil 143, realizing the "pre-single crystallization" of the electrolytic copper foil 600, so that when the finished copper foil is prepared later, the annealing temperature can be significantly reduced, and the finished copper foil can be obtained under low temperature annealing conditions, and because the annealing temperature is reduced, even if the thickness of the electrolytic copper foil 600 is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0048] The material of the body 141 includes but is not limited to stainless steel, titanium, etc. Optionally, the material of the body 141 is titanium, which has good corrosion resistance and long service life.
[0049] The diameter of the body 141 may be 0.1-10 m, and the body 141 may be solid or hollow. Those skilled in the art may configure it according to actual needs, and no limitation is made here.
[0050] The conductive connection between the annular base copper foil 143 and the body 141 includes but is not limited to conductive adhesive bonding. The conductive connection may also be achieved by close contact, laser welding or other high temperature welding techniques.
[0051] In some embodiments, optionally, the thickness of the base copper foil 143 is 25-70 μm, for example, the thickness of the base copper foil 143 is any value of 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, 55 μm, 60 μm, 65 μm or 70 μm, etc. or between any two values. The thickness of the base copper foil 143 is reasonable, which is not only convenient for sleeve installation on the body 141, but also ensures that the surface of the base copper foil 143 formed on the body 141 is smooth. In this embodiment, the thickness of the base copper foil 143 is 50 μm.
[0052] In some embodiments, optionally, the thickness of the graphene film 145 is 20nm≤≤350nm, for example, the thickness of the graphene film 145 is any value of 20nm, 40nm, 50nm, 70nm, 100nm, 130nm, 150nm, 180nm, 200nm, 230nm, 250nm, 280nm, 300nm, 350nm, etc. or between any two values. The thickness of the above-mentioned graphene film 145 is reasonable, and the surface morphology characteristics of the substrate copper foil 143 can be replicated, and the graphene film 145 can be avoided from being damaged when the electrolytic copper foil 600 is peeled off. If the graphene film 145 is too thin, it is easy to cause the graphene film 145 to be easily damaged when the electrolytic copper foil 600 is peeled off. If the graphene film 145 is too thick, it is not conducive to obtaining surface morphology characteristics similar to the substrate copper foil 143. In this embodiment, the thickness of the graphene film 145 is 100μm.
[0053] In this embodiment, there is a conductive adhesive layer (not shown) between the base copper foil 143 and the body 141. That is, the annular base copper foil 143 and the body 141 are bonded with conductive adhesive, and the preparation method is simple.
[0054] The thickness of the conductive adhesive layer is ≤50 μm, and can be selected to be ≤30 μm. For example, in this embodiment, the thickness of the conductive adhesive layer is 30 μm, and the thickness of the conductive adhesive layer is uniform.
[0055] The cathode roller 140 can be manufactured by the following steps:
[0056] A strip-shaped substrate copper foil 143 is obtained, and the material of the strip-shaped substrate copper foil 143 is single crystal copper foil or large crystal domain copper foil; a graphene film 145 is formed on any surface of the strip-shaped substrate copper foil 143; the side of the strip-shaped substrate copper foil 143 away from the graphene film 145 is bonded to the peripheral wall of the main body 141 by conductive adhesive, and the two ends of the strip-shaped substrate copper foil 143 and the two ends of the graphene film 145 are respectively connected by conductive adhesive and polished to form a ring-shaped substrate copper foil 143 with smooth connection, and a ring-shaped graphene film 145.
[0057] It should be noted that the methods of conductively connecting the two ends of the strip-shaped substrate copper foil 143 and the two ends of the graphene film 145 include but are not limited to conductive adhesive connection, and can also be connected by laser or other high-temperature welding methods. Those skilled in the art can make settings according to actual needs and are not limited here.
[0058] The step of forming the graphene film 145 on any surface of the substrate copper foil 143 can be performed by transferring the graphene film 145 to the substrate copper foil 143 using a polymer transfer method. However, in order to avoid unnecessary wrinkles of the graphene film 145 due to the transfer, optionally, the step of forming the graphene film 145 on any surface of the substrate copper foil 143 includes: forming the graphene film 145 on the surface of the substrate copper foil 143 using a chemical vapor deposition method, which can effectively avoid the generation of wrinkles, so that the formed graphene film 145 has surface morphology characteristics similar to those of the substrate copper foil 143.
[0059] The peeling mechanism 160 is used to peel off the electrolytic copper foil 600 on the cathode roller 140 .
[0060] Optionally, the system 10 for preparing the finished copper foil further includes an elastic member (not shown) connected to the cathode roller 140, and the stripping mechanism 160 is configured to be always connected to the cathode roller 140 under the action of the elastic member for stripping the electrolytic copper foil 600 on the cathode roller 140. By using the arrangement of the stripping mechanism 160, the electrolytic copper foil 600 on the cathode roller 140 can be quickly stripped with high stripping efficiency. It should be noted that the stripping mechanism 160 can be a stripping roller or a stripping knife.
[0061] In order to ensure the cleanliness of the finished copper foil, in this embodiment, the system 10 for preparing the finished copper foil further includes a cleaning mechanism 210 and a drying mechanism 300 .
[0062] See also Figure 1 The cleaning mechanism 210 is used to receive and clean the electrolytic copper foil 600 stripped from the stripping mechanism 160 , and the drying mechanism 300 is used to dry the cleaned electrolytic copper foil 600 and transport it to the annealing mechanism 500 .
[0063] Optionally, the system 10 for preparing the finished copper foil further includes a post-processing mechanism 220, which is used to etch the electrolytic copper foil 600 and / or perform an anti-oxidation treatment on the electrolytic copper foil, wherein the post-processing mechanism 220 may be located before the cleaning mechanism 210 to receive the stripped electrolytic copper foil 600, at which time the cleaning mechanism 210 will clean the electrolytic copper foil 600 treated by the post-processing mechanism 220, and the post-processing mechanism 220 may be located between the drying mechanism and the annealing mechanism 500 to treat the dried electrolytic copper foil 600 and then transport it to the annealing mechanism 500. In this embodiment, the post-processing mechanism 220 is located between the cleaning mechanism 210 and the drying mechanism 300 to treat the cleaned electrolytic copper foil 600 and then transport it to the drying mechanism 300.
[0064] Among them, the cleaning mechanism 210, the post-processing mechanism 220 and the drying mechanism 300 can be set up separately, or they can be carried out by using an integrated cleaning, post-processing and drying machine, as long as the order of cleaning, post-processing and drying is limited.
[0065] Optionally, the system 10 for preparing the finished copper foil further includes a winding mechanism 400 , such as a winding roller, which is used to collect the dried electrolytic copper foil 600 .
[0066] The annealing mechanism 500 is specifically a heating furnace, which has an annealing chamber 510 for receiving the dried electrolytic copper foil 600. The annealing mechanism 500 is provided with an inert gas input pipeline (not shown) connected to the annealing chamber 510, a hydrogen input pipeline (not shown), and a heating component (not shown) for heating the annealing chamber 510.
[0067] Optionally, the annealing chamber 510 has a feed end 512 and a discharge end 513 arranged opposite to each other, and the annealing mechanism 500 includes a conveying mechanism disposed in the annealing chamber 510 , and the conveying mechanism is used to convey the dried electrolytic copper foil 600 from the feed end 512 to the discharge end 513 .
[0068] The annealing chamber 510 may be in a strip shape, with a feed end 512 and a discharge end 513 located at two ends of the annealing chamber 510 in the length direction.
[0069] It should be noted that the electrolytic copper foil 600 transported to the annealing chamber 510 during annealing can be a coiled material after winding, or it can be a sliced material that is placed in the annealing chamber 510 in the form of a single sheet or a stack of sheets after slicing the electrolytic copper foil 600, or it can be a strip material that is directly transported to the annealing chamber 510 after the peeled electrolytic copper foil 600 is cleaned and dried.
[0070] Taking the electrolytic copper foil 600 transported into the annealing chamber 510 during annealing as an example, the conveying mechanism includes a high-temperature resistant hanging rail 520 arranged from the feed end 512 to the discharge end 513, and a reeling wheel 530 cooperating with the high-temperature resistant hanging rail 520, and the reeling wheel 530 is used to carry the reel.
[0071] Taking the electrolytic copper foil 600 transported to the annealing chamber 510 during annealing as sliced material or strip material as an example, the conveying mechanism includes a high temperature resistant conveyor belt (not shown) or a high temperature resistant roller (not shown) arranged from the feed end 512 to the discharge end 513, and a high temperature resistant chassis (not shown) matched with the high temperature resistant conveyor belt or the high temperature resistant roller, and the high temperature resistant chassis is used to carry the sliced material or strip material.
[0072] In order to directly transport the stripped electrolytic copper foil 600 to the annealing chamber 510 for annealing, in some embodiments, optionally, the finished copper foil preparation system 10 includes a guide roller, which directly transports the electrolytic copper foil 600 stripped from the stripping roller (without winding) to the cleaning mechanism 200 for direct cleaning.
[0073] The present application example provides a method for preparing an electrolytic copper foil 600, which includes: electrolysis in the above-mentioned electrolytic copper foil mechanism 100, so that the electrolytic copper foil 600 is electrodeposited on the surface of the graphene film 145, and the electrolytic copper foil 600 is peeled off. In the above-mentioned setting method, the operation is simple, and the cathode roller 140 of the electrolytic copper foil mechanism 100 is used to prepare the electrolytic copper foil 600, which is not only conducive to the subsequent peeling of the electrolytic copper foil 600, but also avoids damage to the electrolytic copper foil 600 during peeling. At the same time, the obtained electrolytic copper foil 600 has a surface morphology similar to that of the substrate copper foil 143, and the copper lattice is pre-crystallized, which is conducive to the subsequent low-temperature annealing to directly obtain a single crystal or large crystal domain copper foil as a finished copper foil. At the same time, a single crystal or large crystal domain copper foil with a thickness of less than 25μm can also be directly obtained.
[0074] Optionally, after the cathode roller 140 and the anode are immersed in the electrolyte 130, the electrolysis is performed under the conditions that the rotation speed of the cathode roller 140 is 1-500 mm / min and the current density of the direct current is 0.1-3 ASD.
[0075] The electrolyte 130 is an aqueous solution containing sulfate ions and copper ions. In addition, chloride ions and other additives may be added, which are not specifically limited here.
[0076] The example of the present application provides a method for preparing a finished copper foil, wherein 0≤the number of grain boundaries per square decimeter of the finished copper foil≤5, that is, the finished copper foil is a single crystal copper foil or a large crystal domain copper foil.
[0077] The method for preparing the finished copper foil includes: placing the electrolytic copper foil 600 prepared by the preparation method of the electrolytic copper foil 600 described above in an annealing chamber 510, introducing inert gas and H2 into the annealing chamber 510 and heating, wherein the inert gas flow rate is 300-500sccm; when the temperature is raised to 300-800°C, the inert gas flow rate remains unchanged, H2 is introduced with a H2 flow rate of 10-500sccm, and then annealing is performed for a preset time and then cooled. Since the obtained electrolytic copper foil 600 has a surface morphology similar to that of the substrate copper foil 143, the finished copper foil can be obtained at an annealing temperature of 300-800°C, which can not only effectively reduce energy consumption, but also because the annealing temperature is significantly lower than the existing annealing temperature, even if the thickness of the electrolytic copper foil 600 is less than 25μm, the problem of wrinkling of the copper foil during the annealing process can be avoided, and a single crystal or large crystal domain copper foil with a thickness of less than 25μm can be directly obtained.
[0078] The heating process is from room temperature to annealing temperature, and the heating process lasts for 10-180 minutes.
[0079] The inert gas is, for example, nitrogen, argon or helium.
[0080] Optionally, the annealing temperature is any value of 300° C., 350° C., 400° C., 500° C., 600° C., 700° C., 799° C., 800° C., or between any two values.
[0081] Optionally, the annealing time is 120-350 min, for example, the preset time is any value of 120 min, 130 min, 150 min, 160 min, 200 min, 290 min, 350 min or between any two values. The annealing time can be adjusted according to the thickness of the electrolytic copper foil 600 to ensure that the finished copper foil meets the requirements.
[0082] Optionally, cooling is the natural cooling of the heating chamber after the heating component stops heating.
[0083] Example 2
[0084] The method for preparing the finished copper foil comprises:
[0085] S1. Under the conditions of an electrolyte temperature of 20 to 35° C., a cathode roller rotation speed of 250 mm / min, and a current density of 1 ASD, the cathode roller uses the electrolyte to electroplatingly deposit electrolytic copper foil, and a stripping roller continuously strips off an electrolytic copper foil having a length of 0.5 m and a thickness of 5 μm from the graphene film surface of the cathode roller. The electrolytic copper foil is cleaned and dried, and then wound to obtain an electrolytic copper foil coil.
[0086] The concentration of CuSO4 in the electrolyte is 130g / L, the concentration of H2SO4 is 90g / L, and the concentration of Cl - The concentration is 50ppm.
[0087] S2. Feed the electrolytic copper foil coil onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, and transport the electrolytic copper foil coil from the discharging end to the feeding end. At the same time, introduce argon with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 780°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, and only introduce argon. Cool to room temperature and reel.
[0088] Example 3
[0089] The method for preparing the finished copper foil comprises:
[0090] S1. Under the conditions of an electrolyte temperature of 20 to 35° C., a cathode roller rotation speed of 220 mm / min, and a current density of 1 ASD, the cathode roller uses the electrolyte to electroplatingly deposit electrolytic copper foil, and a stripping roller continuously strips off an electrolytic copper foil having a length of 0.5 m and a thickness of 6 μm from the graphene film surface of the cathode roller. The electrolytic copper foil is cleaned and dried, and then wound to obtain an electrolytic copper foil coil.
[0091] The concentration of CuSO4 in the electrolyte is 130g / L, the concentration of H2SO4 is 90g / L, and the concentration of Cl - The concentration is 50ppm.
[0092] S2. Feed the electrolytic copper foil coil onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, and transport the electrolytic copper foil coil from the discharging end to the feeding end. At the same time, introduce argon with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 780°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, and only introduce argon. Cool to room temperature and reel.
[0093] Example 4
[0094] The method for preparing the finished copper foil comprises:
[0095] S1. Under the conditions of an electrolyte temperature of 20 to 35° C., a cathode roller rotation speed of 50 mm / min, and a current density of 1 ASD, the cathode roller uses the electrolyte to electroplatingly deposit electrolytic copper foil, and a stripping roller continuously strips off the graphene film surface of the cathode roller to obtain an electrolytic copper foil with a length of 0.5 m and a thickness of 25 μm. After the electrolytic copper foil is cleaned and dried, it is wound to obtain an electrolytic copper foil coil.
[0096] The concentration of CuSO4 in the electrolyte is 130g / L, the concentration of H2SO4 is 90g / L, and the concentration of Cl - The concentration is 50ppm.
[0097] S2. Feed the electrolytic copper foil coil onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, and transport the electrolytic copper foil coil from the discharging end to the feeding end. At the same time, introduce argon with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 780°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, and only introduce argon. Cool to room temperature and reel.
[0098] Example 5
[0099] The method for preparing the finished copper foil comprises:
[0100] S1. Under the conditions of electrolyte temperature of 20-35°C, cathode roller rotation speed of 65mm / min, and current density of 0.1-3ASD, the cathode roller uses the electrolyte to electroplating electrolytic copper foil, and the stripping roller continuously strips the graphene film surface of the cathode roller to obtain an electrolytic copper foil with a length of 1m and a thickness of 20μm. After the electrolytic copper foil is cleaned and dried, it is wound to obtain an electrolytic copper foil coil. The concentration of CuSO4 in the electrolyte is 130g / L, the concentration of H2SO4 is 90g / L, and the concentration of Cl - The concentration is 50ppm.
[0101] S2. Feed the electrolytic copper foil coil onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, and transport the electrolytic copper foil coil from the discharging end to the feeding end. At the same time, introduce argon with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 780°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, and only introduce argon. Cool to room temperature and reel.
[0102] Example 6
[0103] The only difference between it and Example 5 is: S2, feed the electrolytic copper foil coil with a thickness of 6 μm onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, and transport the electrolytic copper foil coil from the discharge end to the feed end, while introducing argon gas with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 550°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, only introduce argon gas, cool to room temperature, and roll up.
[0104] Example 7
[0105] The only difference between it and Example 5 is: S2, feed the electrolytic copper foil coil with a thickness of 6 μm onto the unwinding wheel in the annealing chamber of the annealing mechanism, close the annealing chamber, transport the electrolytic copper foil coil from the discharge end to the feed end, and at the same time, introduce argon with a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 150 minutes) to 800°C, the argon flow rate remains unchanged, and H2 is introduced with a flow rate of 100 sccm to start annealing. After annealing for 300 minutes, turn off the heating power supply, stop introducing other gases, only introduce argon, cool to room temperature, and roll up.
[0106] Comparative Example 1
[0107] The only difference between it and Example 2 is that the cathode roller is made of pure titanium.
[0108] Comparative Example 2
[0109] The only difference between it and Example 2 is that in the cathode roller, the annular base copper foil is a polycrystalline rolled copper foil, and the number of grain boundaries per square decimeter is greater than 50.
[0110] Comparative Example 3
[0111] The only difference between it and Example 2 is that the material of the cathode roller is pure titanium, and in step S2, the electrolytic copper foil coil is fed into the unwinding wheel in the annealing chamber of the annealing mechanism, the annealing chamber is closed, the electrolytic copper foil coil is transported from the discharge end to the feed end, and argon gas is introduced at a flow rate of 300 sccm. When the temperature is raised (the heating process lasts for 180 minutes) to 1000°C, the argon flow rate remains unchanged, H2 is introduced at a flow rate of 100 sccm to start annealing, and after annealing for 300 minutes, the heating power is turned off, and other gases are stopped from being introduced. Only argon gas is introduced, and it is cooled to room temperature and rolled up.
[0112] Test Example 1
[0113] The finished copper foils obtained in Examples 2-7 and Comparative Examples 1-3 were cut to obtain 10 cm*10 cm samples, and the samples were measured using a four-terminal conductivity meter; 50 pieces of the finished copper foils prepared in Examples 2-7 and Comparative Examples 1-3 were randomly selected, and the probability of samples with wrinkles that were significantly visible to the naked eye was counted as the wrinkle rate. The results are shown in Table 1.
[0114] Table 1 Test results
[0115] Conductivity (IACS%) Wrinkle rate (%) Example 2 103.5%IACS 6% Example 3 105.3%IACS 4% Example 4 104.8%IACS 2% Example 5 104.3%IACS 2% Example 6 100.7%IACS 2% Example 7 104.5%IACS 6% Comparative Example 1 98.2%IACS 80% Comparative Example 2 98.6%IACS 84% Comparative Example 3 102.9%IACS 96%
[0116] It can be seen from Table 1 that the conductivity of the finished copper foil prepared in the embodiment is significantly better than that of the comparative examples 1-3, and the wrinkle rate is significantly reduced.
[0117] At the same time, XRD tests were performed on the samples of Examples 2-3 and Comparative Example 1. The results are as follows: Figure 3 , Figure 4 as well as Figure 5 shown.
[0118] according to Figure 3 as well as Figure 4 It can be seen that the finished copper foils prepared in Example 2 and Example 3 have characteristic XRD peaks of single crystal copper. Figure 5 It can be seen that the finished copper foil prepared in Comparative Example 1 does not have the characteristic XRD peak of single crystal copper.
[0119] In summary, when the cathode roller provided by the present application is applied to an electrolytic copper foil mechanism to prepare an electrolytic copper foil, the electrolytic copper foil can replicate the surface morphology characteristics of the graphene film, thereby making its crystal domain and grain boundary distribution similar to those of the substrate copper foil, thereby realizing "pre-crystallization" of the electrolytic copper foil, so that when single crystal or large crystal domain copper foil is subsequently prepared, the annealing temperature can be significantly reduced, and single crystal copper foil or large crystal domain copper foil can be obtained under low temperature annealing conditions, and since the annealing temperature is reduced, even if the thickness of the electrolytic copper foil is less than 25μm at this time, a finished copper foil with a low wrinkle rate that meets relevant requirements can be obtained.
[0120] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a finished copper foil, characterized in that: 0≤The number of grain boundaries per square decimeter of the finished copper foil is ≤5; The preparation method comprises: placing an electrolytic copper foil in an annealing chamber, introducing an inert gas into the annealing chamber and raising the temperature, wherein the inert gas flow rate is 300-500 sccm; When the temperature is raised to 300-800°C, the inert gas flow rate remains unchanged, H2 is introduced with a H2 flow rate of 10-500 sccm, and then cooled after annealing for a preset time; The thickness of the electrolytic copper foil is less than 25 μm. The preparation of the electrolytic copper foil includes: An electrolytic copper foil structure is obtained, the electrolytic copper foil structure comprising an electrolytic cell, a cathode roller and an anode part, the electrolytic cell is used to hold an electrolyte, the cathode roller uses the electrolyte to deposit electrolytic copper foil by electroplating, and the anode part is energized with the cathode roller through the electrolyte; wherein the cathode roller comprises: a roller-shaped body, an annular substrate copper foil and a graphene film, the substrate copper foil is formed on the peripheral wall of the body and is conductively connected to the body; the graphene film is formed on the surface of the substrate copper foil and replicates the surface morphology of the substrate copper foil; the substrate copper foil is made of single crystal copper foil or large crystal domain copper foil, and the number of grain boundaries of the large crystal domain copper foil per square decimeter is ≤5; After the cathode roller and the anode are immersed in an electrolyte, electrolysis is performed to deposit an electrolytic copper foil on the surface of the graphene film, and the electrolytic copper foil is peeled off.
2. The preparation method according to claim 1, characterized in that: The preset time is 120-350 minutes.
3. The preparation method according to claim 1, characterized in that: The thickness of the electrolytic copper foil is 4.5-8 μm.
4. The preparation method according to claim 1, characterized in that: The thickness of the base copper foil is 25-70 μm.
5. The preparation method according to claim 1, characterized in that: 20nm≤The thickness of the graphene film is ≤350nm.
6. The preparation method according to claim 1, characterized in that: A conductive adhesive layer is provided between the base copper foil and the body.
Citation Information
Patent Citations
Composite board, preparation method thereof and vapor chamber
CN112760644A
Electric heating treatment device for reducing warping of copper foil
CN113151759A
Cathode roller, electrolytic copper foil mechanism and preparation system of finished copper foil
CN216006045U
Cathode roll for electroforming use, apparatus for forming electoforming thin films and apparatus for forming flexible elctrode substrate comprising the same
KR101681485B1